PRA RANCANG PABRIK ARANG AKTIF DARI BAMBU DENGAN SISTEM FAST PYROLISIS DENGAN KAPASITAS 5000 TON/TAHUN - Ian Fransiskus Lerrick; Taufik Iskandar (Universitas Tribhuwana Tunggadewi Malang, 2016)
The raw material for the manufacture of activated charcoal is very abundant. The raw materials can be made into activated charcoal is any substance containing carbon, both derived from plants, animals, and minerals such as coal. Bamboo so far is only used as an interior material and also with in the development period bamboo is used as an ingredient raw craft. To increase the added value of bamboo, bamboo utilization efforts are required to be processed into charcoal, through pyrolysis technology. Pyrolysis is the thermal decomposition process of biomass with limited oxygen and high temperature. For particles of 5-8 mm, the composition of the pyrolysis are 5% Tar, 46.82% Char, 7% gas, 41.18% liquid smoke. Pyrolysis is the thermal decomposition process of biomass with limited oxygen. Pyrolysis release of three kinds of products: solid, liquid, and gas. Pyrolysis release of three kinds of products: solid, liquid, and gas. Pre-planning design of activated bamboo charcoal by fast pyrolysis system. This design will be established in Riau. Pre activated charcoal design with Fast Pyrolysis system with bamboo will be built in 2016 with a capacity of 5000 t/year. Activated Charcoal Making Process consists of: Preparation, the process of pyrolysis and activation processes, Based on economic analysis, industrial activated charcoal is feasible to set up views of the economic aspects as follows: ROIat (%): 55.01%, POT (Years): 1 , 41, BEP (%): 34.96%, the IRR (%): 44.60.